Maintenance of highway elevated structure in Malaysia / Nadeah Khairunnisa Noor Kamal - Noor Kamal, Nadeah Khairunnisa (Faculty of Architecture, Planning and Surveying, 2010)
Elevated highway structure is a bridge that linked 2 roads that have obstacles in between them. It is solution for traffic congestion and also to support the numbers of vehicles that increase from day to day. This elevated structure has it own design and need proper maintenance to ensure safety for the users. This research was made with the objective to study the regulation that relates to the highway elevated structure in Malaysia to identify what are the procedures must be taken when carried out maintenance to the highway elevated structure and to study how the maintenance works are carried out. This study was carried out by doing interview with civil engineer of 3 cases study to know the procedure of maintenance work and also research was made from the past maintenance report. From this research, the maintenance guideline use for the maintenance procedure was adapted from Road Engineering Association of Malaysia and Jabatan Kerja Raya Malaysia.